Burn-out syndrome and teacher job satisfaction - Raciala (Pohaci), Alexandra; Rus, Mihaela; Sandu, Mihaela Luminita; Rus, Ciprian Vasile (Technium Social Sciences Journal, 2021)
The concept of burnout is often used when trying to explain the state of chronic stress in people working in a field that involves contact with people, such as, in our case, education. Teachers spend a long time at work and are involved in multiple relationships: both with students, colleagues (other teachers, principals), and with other parents. All these various interactions require a mental and even physical effort. Also, teaching and assessment activities consume energy and require considerable effort. Thus, the resources needed by the teacher (time, financial), work and performance requirements can erode the teacher’s energy and enthusiasm, which sometimes leads to the manifestation of burnout symptoms. Burnout is “a state of chronic fatigue, depression and frustration generated by the devotion of a cause, a way of life or a relationship that fails to produce the expected rewards and ultimately leads to diminished involvement and work” (Zlate, 2007 , pp. 598 in Richelson, 1980.